2013
DOI: 10.1002/jmri.24535
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of oxygen‐enhanced T1 mapping MRI of the lung: Reproducibility and impact of closed versus loose fit oxygen delivery system

Abstract: Oxygen-enhanced T1 mapping MRI produces reproducible data when using a full closed face mask.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 26 publications
(42 reference statements)
2
28
0
Order By: Relevance
“…The average T1 at end tidal inspiration in this study was 1185 ms (16 male, 14 females, mean age 38, TE = 0.67 ms) which is well in line with the mean lung T1 reported in earlier publications by Stadler: 1199 ms (8 male, 2 female, mean age 30, end‐inspiration, TE = 1.4 ms); Alamidi: 1053 ms (8 male, 4 female, mean age 63, TE = 3 ms, free breathing, spin echo); and Renne: 1250 ms (7 male, 5 female, mean age 28, TE 0.8, end‐inspiration) …”
Section: Discussionsupporting
confidence: 90%
“…The average T1 at end tidal inspiration in this study was 1185 ms (16 male, 14 females, mean age 38, TE = 0.67 ms) which is well in line with the mean lung T1 reported in earlier publications by Stadler: 1199 ms (8 male, 2 female, mean age 30, end‐inspiration, TE = 1.4 ms); Alamidi: 1053 ms (8 male, 4 female, mean age 63, TE = 3 ms, free breathing, spin echo); and Renne: 1250 ms (7 male, 5 female, mean age 28, TE 0.8, end‐inspiration) …”
Section: Discussionsupporting
confidence: 90%
“…However, with the presented technique based on higher-spatial-resolution images for vessel detection, sufficient accuracy should be reached. In previous work, it has been shown that T1 time determination for the lungs is reproducible using this technique (23). Furthermore, statistical power is limited, because of the relatively small number of patients, and studies with more patients are needed to underline the presented findings.…”
Section: Discussionmentioning
confidence: 91%
“…Three to four coronal sections covering the challenged segments were acquired in a single breath hold each. The subjects were instructed to breathe normally and stop breathing at the end of a normal inspiration (23). T1 maps were obtained while the patient was breathing room air and again while the patient was breathing 100% oxygen administered by using a standard face mask with a reservoir of 2 L (Adult Non Re-Breather Mask; Mallinkrodt Covidien, Mansfield, Mass) (24).…”
Section: Mr Imaging Sequences and Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Both respiratory and cardiac triggering have been implemented successfully for 2D OE‐MRI . Typically, nonrebreather facemasks are used with a constant flow of oxygen at 15 L/min . Even with the use of respiratory gating or triggering, lung volume can vary with changes in the fraction of inhaled O 2 .…”
Section: Tradeoffs In Cost and Accessmentioning
confidence: 99%